2014
DOI: 10.1002/cbin.10268
|View full text |Cite
|
Sign up to set email alerts
|

Tolerogenic dendritic cells suppress murine corneal allograft rejection by modulating CD28/CTLA‐4 expression on regulatory T cells

Abstract: Anterior chamber-associated immune deviation (ACAID) is initiated when dendritic cells (DCs) capture intraocular antigen and induce regulatory T cells (Tregs) in the spleen. We investigated whether DCs could be used as an immunotherapy to prevent murine corneal allograft rejection by inducing Tregs. Bone marrow-derived DCs (BMDCs) were differentiated with transforming growth factor-β2 (TGF-β2) in the presence of donor-derived allopeptide in vitro (TGFβ2-DCs), and adoptively transferred to BALB/c mice. Three da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 46 publications
0
15
0
2
Order By: Relevance
“…Studies on murine models of penetrating keratoplasty have demonstrated that administration of donor-derived tolDCs to hosts prior to transplantation increases the frequencies of Foxp3 hi Tregs and significantly improves corneal allograft survival (109). Results of a recent study indicate that the beneficial effect of tolDCs on corneal graft survival is mediated through expansion of CTLA-4 expressing Tregs and downregulation of CD28 + Tregs (110). Given that tolDCs induce allotolerance primarily through Treg expansion, the majority of studies have focused on modification of Treg function to promote graft survival.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on murine models of penetrating keratoplasty have demonstrated that administration of donor-derived tolDCs to hosts prior to transplantation increases the frequencies of Foxp3 hi Tregs and significantly improves corneal allograft survival (109). Results of a recent study indicate that the beneficial effect of tolDCs on corneal graft survival is mediated through expansion of CTLA-4 expressing Tregs and downregulation of CD28 + Tregs (110). Given that tolDCs induce allotolerance primarily through Treg expansion, the majority of studies have focused on modification of Treg function to promote graft survival.…”
Section: Introductionmentioning
confidence: 99%
“…The sTGF-2 on the B cells was reported to decrease the expression of CD69, CD40, CD80, CD86, and MHC II molecules on the B cells. 16,17 Therefore, we may presume that TIO3 could increase the expression of CD69, CD40, CD80, CD86, and MHC II molecules on the Tregs. 60,61 The data suggest that the sTGF-2 could be an inhibitory molecule to attenuate humoral immune responses to vaccines by promoting Treg generation.…”
Section: Discussionmentioning
confidence: 99%
“…Фенотип ДК также был охарактеризован определением экспрессии еще 3-х маркеров: CD80, CD86 и HLA-DR. CD80 (B7-1, B7 и BB1) и CD86 (B7-2, B70 и Ly-58) представляют собой гликопротеины, принадлежащие к суперсемейству иммуноглобулинов, с массой, соответственно, 60 и 80 кДа. Доказано, что взаимодействие CD80 и CD86 на ДК с CD28 обеспечивает мощный костимуляторный сигнал для активации Т-лимфоцитов, тогда как их взаимодействие с CTLA-4 обеспечивает ингибирующий сигнал для Т-клеток [9,31]. HLA-DR (антиген главного комплекса гистосовместимости II класса) является гетеродимерным гликопротеином, который экспрессируется на многих типах клеток иммунной системы, для ДК является критическим для осуществления эффективной антигенпрезентации [6,8].…”
Section: Discussionunclassified